THE ADVANTAGES OF WUDHU FOR SOME CONTEMPORARY PROBLEMS - Adinda Putri Alim; Albazar .; Triya Marselina .; Zaim Rais (MADDIKA : Journal of Islamic Family Law, 2020)
This article aims to discuss the Hadast (excretion) and najis that are an obstacle for us to perform worship to Allah SWT. Repeating the study of taharah and najis in Islamic Fiqh will make us find a rule and discussion that we have never known before. It is necessary to Clean or clean first to worship to the maximum To get rid of the Hadast and unclean. Clean signals that we should always clean our souls from sin and all vile deeds. Clean is performed not only to achieve worship but also to maintain the cleanliness and health of the human body. We are required to know all the ins and outs of Clean and practice it correctly. There are still many Muslims who even do not understand Clean. The procedure of Clean has been mentioned in fiqh books in great detail. Always, with the method of content analysis and qualitative approach, the author tries to dig back into something that is rarely touched by fiqh books in general. In the reading of Pustaka, the author obtains the status of animal faeces that are halal eaten by the meat; it turns out that the wastes are not unclean according to various sects such as Malikyah and Hanabilah. So far, many people think that the faeces of chickens, goats, cows, and other livestock ate are unclean and can cancel Clean. Contemporary problems arise around Clean, such as a person whose body is full of tattoos and challenging to get rid of for the sake of his hifz An-Nafs Wudu 'remains if the tattoo can not be removed. Taharah has many other benefits, such as preventing Covid-19